NEW RECORD OF FRESHWATER ERITHISTID CATFISH CONTA CONTA (HAMILTON, 1822) (TELEOSTEI: ERETHISTIDAE) FROM ARUNACHAL PRADESH (BIODIVERSITY HOTSPOT), INDIA - KENTO KADU; DEBANGSHU NARAYAN DAS (The Bioscan, 2011)
A small catfish species Conta conta (Hamilton) has been recorded for the first time from the water bodies of the Arunachal Pradesh (AP), India. The species is characterized by the presence of elongated adhesive apparatus, serration on both edges of the dorsal fin spine and slender caudal peduncle region. It is easily distinguished from its nearest congeners C. pectinata Ng, 2005 in having distally directed vs. anteriorly-directed serrations on the anterior edge of the pectoral spine. A review of literature shows that there is no report of the species from the water bodies of the state. The present paper deals with the first record of Conta conta (Hamilton) from the state and brief description of the species and its geographical distribution up to the state of A. P.